Perancangan Sistem Informasi Klien Dewasa Pada BAPAS Kelas 1 Palembang - Raka Ramadhan; Evi Fadilah (Prosiding SISFOTEK, 2025)
This study aims to design an information system for adult clients at the Class I Correctional Center (Bapas) Palembang using the Prototyping method. The background of this research lies in the limitations of the existing Correctional Database System (SDP) which has not fully supported the operational needs of the Adult Client Guidance Section (BKD), especially in managing attendance records, Litmas archiving, and preparing periodic reports. Data were collected through observation and interviews with BKD officers, then analyzed to identify system requirements. The Prototyping method was applied through iterative stages, starting from communication, quick planning, design modeling, construction, and user feedback. The results of the design produced a prototype consisting of eight main interfaces, including client data management, attendance schedules, Litmas archives, and monthly reports. This prototype provides added value in terms of efficiency, accuracy, and ease of use for BKD officers, even though it is still limited to the design stage and has not yet been integrated with SDP. The findings of this research are expected to serve as a basis for the development of a more comprehensive system in the future.